Beyond the harsh : objective and subjective living conditions in Nunavut - Morin, Alexandre; Édouard, Roberson; Duhaime, Gérard (Polar Record, 2024)
This paper simultaneously analyses some objective and subjective living conditions in Nunavut (federal territory of Canada located in the Arctic) in 2001: population, housing, language, education, economic activities, health, social problems and geographic mobility. It examines original descriptive statistics from the Survey of living conditions in the Arctic and other sources. In some cases the results confirm the ordinary depressing picture of Inuit conditions, but in other cases statistics qualify or even contradict such a picture. The overall findings show that despite objective difficult conditions, Nunavummiut living in Nunavut (primarily the elites and the lower class) are generally satisfied with their communities so that the majority wishes to remain there. Certain modern social institutions and individual rationalities are contributing to this situation: wage earning, market economy, utilitarian and consumption oriented approach, democratic state based on law, formal knowledge, individualism and the capacity for self analysis. The concepts of aspiration and mastery of one's own destiny seem accurate to explain the importance of education and employment in people's satisfaction, and their dissatisfaction about the housing situation. The existence of family and neighbourhood networks appears to explain both a certain residential stability and out migration, through the social support functions of these networks, in which sharing and exchanging food play a major role. In general, if most of Nunavummiut continue to live in the Arctic despite unfavourable conditions, it is not only because they are able to ensure their material existence there, but also because they attach a meaning to and believe that that is where they have the best chance to exert the highest degree of control over their personal and domestic reality.